Eliminating bullying and harrassment from the aged care environment - Curran, Mairead; Baricevic, Thomas (Video Education Australasia, 2007)
"People working in aged care routinely provide love, care and support for the elderly but often they can be less than caring and supportive of each other. This program examines the definitions, types and ramifications of workplace bullying and harassment. The program will also assist employees to identify when they, and others, are being subjected to unfair workplace behaviour and, more importantly, what they can do to stop it and prevent its recurrence, thereby creating a safer, happier and more productive workplace for all."